1955
DOI: 10.1099/00221287-13-1-136
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Aerial Mycelium and other Changes in Streptomycete Development due to Physical Variations of Cultural Conditions

Abstract: SUMMARY : Several isolates of monosporous lines of Streptomyces coelicolor, both normally pigmented and colourless variants, were obtained by microdissection of young vegetative mycelia. In each case their properties largely resembled those of the parents. This material was studied together with three strains of Streptomyces scabies of varying degrees of virulence, which had been isolated from potato scab lesions. Modifications of growth were noted with respect to gross colonial morphology on agars containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1958
1958
1999
1999

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…According to these authors, there are three types of organs which initiate new mycelial growth: 1) "segmentation spores" formed in a vegetative phase of mycelial growth; 2) long cylindrical structures termed "birches" which appear to be occasionally formed during a sporulation phase; and, 3) "conidia" arising from "elements speciforme" or "massues" which develop in the same sporulation phase. Erikson (1955) studied Streptomyces coelicolor and Streptomyces scabies and observed a variety of different cell types. She interpreted some to be the result of cultural conditions and some the artefacts of staining.…”
Section: Discussionmentioning
confidence: 99%
“…According to these authors, there are three types of organs which initiate new mycelial growth: 1) "segmentation spores" formed in a vegetative phase of mycelial growth; 2) long cylindrical structures termed "birches" which appear to be occasionally formed during a sporulation phase; and, 3) "conidia" arising from "elements speciforme" or "massues" which develop in the same sporulation phase. Erikson (1955) studied Streptomyces coelicolor and Streptomyces scabies and observed a variety of different cell types. She interpreted some to be the result of cultural conditions and some the artefacts of staining.…”
Section: Discussionmentioning
confidence: 99%
“…However, it could not be substantiated. Erikson (1955) had found that aerial hyphae of the A3(2) strain arose as simple side-branches of vegetative hyphae anywhere over the colonies. I confirmed this (Fig.…”
Section: Does Streptomyces Have a Life Cycle ?mentioning
confidence: 99%
“…1). S. coelicolor A3(2), a strain isolated independently (14) and the subject of most genetic work, was also found to produce actinorhodin (18,40), but related pigments were not sought. The pH-dependent color transition of actinorhodin, exploited to isolate mutants of S. coelicolor A3(2) impaired in actinorhodin biosynthesis (35), has been used extensively for cloning and mapping of the act gene cluster (16,29,30).…”
mentioning
confidence: 99%